2016
DOI: 10.5539/ijps.v8n3p26
|View full text |Cite
|
Sign up to set email alerts
|

Validation Evidence for the Work Domain Satisfaction Scale in Two Languages

Abstract: We used the samples of six studies to validate the Work Domain Satisfaction Scale (WDSS), a global, five-item and mid-level measure of work domain well-being. English and French versions of the scale were included in the studies to assess the stability of the instrument across these languages. Confirmatory factor analysis yielded a one-factor structure, which was shown invariant across languages and samples. Test-retest reliability of the scale was high, indicating that it measures a stable construct over time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 49 publications
0
13
0
3
Order By: Relevance
“…We used the French-validated version of the Work Domain Satisfaction Scale (Bérubé, Donia, Gagné, Houlfort, & Lvina, 2016) to assess participants’ work satisfaction. A sample item was “The conditions in which I do my work are excellent.” Items were scored on a 7-point Likert scale, ranging from 1 ( do not agree at all ) to 7 ( very strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
“…We used the French-validated version of the Work Domain Satisfaction Scale (Bérubé, Donia, Gagné, Houlfort, & Lvina, 2016) to assess participants’ work satisfaction. A sample item was “The conditions in which I do my work are excellent.” Items were scored on a 7-point Likert scale, ranging from 1 ( do not agree at all ) to 7 ( very strongly agree ).…”
Section: Methodsmentioning
confidence: 99%
“…Job satisfaction questions were adopted from Brayfield and Rothe [40] and Macdonald and Maclntyre [41], mental stress questions were adopted from Lovibond [42], workload questions were adopted from Caplan [43] and Rizzo, et al [44], organizational relationship questions were adopted from Macdonald and Maclntyre [41] and Settoon and Mossholder [45], job security section was adopted from Hellgren, et al [46], and questions related to workers' perceptions of safety were adopted from Hayes, et al [47]. These scales are extensively used in previous studies and it was confirmed that these all scales have good reliability in term of internal consistency and test-retest reliability [48][49][50][51][52][53][54][55][56].…”
Section: Research Approach and Construction Of The Hypothetical Modelmentioning
confidence: 99%
“…Diener (1994) considers satisfaction to represent the cognitive component of one's well-being, and affect to represent its emotional counterpart, while, according to Helliwell, Layard and Sachs (2013), life satisfaction is a significant contributor to subjective well-being. Similarly, work satisfaction refers to cognitive appraisal of a person's work (Bérubé et al, 2016), and it differs from job satisfaction which refers to the employees' feelings and thoughts about their specific work (Irving & Montes, 2009;Weiss, 2002). This research, in consistency with life satisfaction, and, considering that the participants have a certain career in the certain domain of education, focuses on work satisfaction.…”
Section: Association Of Life Satisfaction and Work Satisfaction With mentioning
confidence: 99%
“…The Satisfaction With the Work Scale (SWWS, Bérubé et al, 2007;Bérubé et al, 2016) was used to examine the participants' work satisfaction. This scale, which was adapted from the Satisfaction with Life Scale (Diener et al, 1985), is a reliable and valid measure of work satisfaction, and it focuses on the cognitive appraisal of a person's work situation.…”
Section: Work Satisfactionmentioning
confidence: 99%
See 1 more Smart Citation